Palm Kernel Oil Residue (PKOR) as livestock feed in Ghana: A case study of four (4) districts in the central region - Gyamera, Ebenezer (University of Cape Coast, 2010)
Feed costs amount to about 70 – 80% of the total production costs of meat production in intensively managed production systems. In Ghana, the major ingredients of such feeds are maize, wheat bran and protein based concentrates based on fishmeal. Agro Industrial By-Products especially Palm Kernel Oil Residue (PKOR) is potentially useful as an energy and/or protein source for feeding all species of livestock. The study was therefore designed to examine the extent of use of PKOR in four districts in the Central Region of Ghana. Primary data were collected using a set of structured and validated interview schedule from 60 poultry and livestock farmers, who were selected using multi-stage sampling technique. Data analysis was carried out using descriptive statistics (frequency counts and percentages) and inferential statistics (Pearson correlation). The results of the analysis showed that the poultry sub-sector was the main user of PKOR. A quarter (25.0%) of farmers sampled in the study use PKOR while 28.3% use a close variant of PKOR called Palm KernelCake. Farmers perceived that using PKOR reduces feed cost than using conventional feed ingredients only or commercially prepared feeds. Empirically, education and type of enterprise showed positive relationship with use of PKOR while years of experience showed negative relationship with use of PKOR. The major recommendations that emanated from the study are: information leaflets containing feed formulation using PKOR for different species of farm animals should be published by the Animal Production Directorate and distributed to farmers, and extension agents should train farmers on best ways of handling and using PKOR for feed.
xii,103p.:ill
Keywords: Palm kernel oil residue; livestocck feed; Palm kernel oil feed